TECHNOLOGICAL OPPORTUNITIES SURVEY OF FOREST SHORT ROTATION PLANTATIONS IN BULGARIA FOR ENERGY BIOMASS PRODUCTION* PART 3: ANALYSIS OF THE TECHNOLOGIES AND MACHINES FORWOOD BIOMASS PLANTATION HARVESTING (Innovation in Woodworking Industry and Engineering design, 2026)
The present survey analyzes the key technologies for harvesting SRC plantation for production of biomass and the typical harvesters, suitable for willow, poplar and black locust harvesting in Bulgaria. The advantages and disadvantages of the various technological schemes are highlighted and some recommendations to the Bulgarian producers on their application are made.